2016
DOI: 10.2147/ndt.s116811
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and self-esteem: testing direct and indirect relationships associated with psychological and physical mechanisms

Abstract: In the present study, we investigated the relationship between physical activity (PA) and self-esteem (SE), while introducing body mass index (BMI), perceived physical fitness (PPF), and body image (BI) in adults (N =264, M =38.10 years). The findings indicated that PA was directly and indirectly associated with SE. BMI predicted SE neither directly nor indirectly, but was directly associated with PPF and both directly and indirectly with BI. Furthermore, PPF was directly related to BI and SE, and a direct ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 48 publications
10
94
1
11
Order By: Relevance
“…In the case of direct effects, physical activity has been identified as significantly related to self-esteem [4] and an important factor for enhancing it. The present study shows that students who are engaged in physical activity have a greater level of self-esteem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of direct effects, physical activity has been identified as significantly related to self-esteem [4] and an important factor for enhancing it. The present study shows that students who are engaged in physical activity have a greater level of self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is commonly described in terms of hopelessness, difficulty concentrating, lack of energy, agitation, restlessness, feelings of worthlessness or pessimism, and suicidal ideation [25]. However, there are a few studies on the relation between depression and physical activity on university students as most of the studies have been conducted on children and adolescents from different age groups linking their academic improvements with increasing physical activity [4]. The literature revealed that physical activity and exercise have constructive effects on depression [26].…”
Section: Physical Activity and Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Como resultado de altos porcentajes de baja autoestima en la muestra evaluada, se hace referencia a los expuesto por Shriver, et al, (2013) que comenta que la población infantil con baja autoestima es susceptible a desórdenes de alimentación, trastornos de la imagen corporal, lo que le impediría desarrollar una vida satisfactoria y exitosa, contribuye al deterioro del bienestar psicológico de los niños (Hojjat, et al, 2016) y a la afectación de los factores psicosociales (Contreras-Valdez, Hernández-Guzmán y Freyre, 2016). Estas dificultades psicológicas son cada vez más comunes en edades tempranas en una sociedad donde la identidad personal y la presión social, continúan siendo un referente para la población en general, independientemente de la edad (Sánchez y Ruiz, 2015;Taberno, Serrano y Mérida, 2017).…”
Section: Resultsunclassified